KONSEP DAN INTEGRASI ILMU-ILMU SOSIAL DALAM IPS - Wasino, Wasino (Jurnal Sejarah dan Budaya, 2010)
Abstract: Allienation between Social studies in Indonesia nowadays caused by inconspicuous subject than other subjects. There are many factors that social studies became pathetic, such as society imaging about social studies, social studies subjects allocation among the schools, teachers performance and confidence, unavailable teacher for integrated social studies subject in junior high scholls and confused content standardization. Social studies need improvement towards better quality. In fact, Social studies in Indonesia influence by Americaâs that given integrated pespective for social studies. Should be, Indonesia applying integrated social studies in school. There are two models to integrate social studies, Social Phenomenon and topics from the subject depends on the points of view. Integrated learning for Social studies education is needed in University as best sollution into this problems nowadays